Anodic dissolution growth of metal–organic framework HKUST-1 monitored via in situ electrochemical atomic force microscopy. Issue 31 (27th June 2018) - Worrall, Stephen D.; Bissett, Mark A.; Attfield, Martin P.; Dryfe, Robert A. W.
Abstract : Real time imaging of the electrochemical growth of metal–organic framework coatings using in situ atomic force microscopy. Abstract : In situ electrochemical atomic force microscopy (ec-AFM) is utilised for the first time to probe the initial stages of metal–organic framework (MOF) coating growth via anodic dissolution. Using the example of the Cu MOF HKUST-1, real time surface analysis is obtained that supports and verifies many of the reaction steps in a previously proposed mechanism for this type of coating growth. No evidence is observed however for the presence or formation of Cu2 O, which has previously been suggested to be both key for the formation of the coating and a potential explanation for the anomalously high adhesion strength of coatings obtained via this methodology. Supporting in situ electrochemical Raman spectroscopy also fails to detect the presence of any significant amount of Cu2 O before or during the coating's growth process.